PENGARUH KONSUMSI TEMPE KEDELAI HITAM TERHADAP BERAT BADAN TIKUS - Nurrahman - -; Nurhidajah - - (Universitas Muhammadiyah Semarang, 2014)
Tempe derived from vegetable material has high quality proteins, good disgestibility, low antinutritional as phytate acid, oligosaccharides and a good source of vitamin of complex B. Thepurpose of this study was to know the effect of black soybean tempe consumption on the weightof rat. A total of 30 rats were grouped into five groups based on a formula feed, that feedstandard AIN 93 and feed that were added black soybean tempe flour 25, 50, 75 and 100percent (instead of casein). Adlibetum feeding in maintenance for 30 days and every 2 daysbeing weighed. The research result was group of rats that eats the feed formula containingblack soybean tempe weight growth higher than standard. There was a tendency the highercontent of black soybean tempe higher growth also. Highest weight growth occurred in thegroup of rats that consumed feed with formula with 75 percent of black soybean tempe.